Solve the following equation: x^(3) - 6x^(2) + 11x - 6 = 0

x3 - 6x2 + 11x - 6 = 0
Let (x-a)(x-b)(x-c) = x3 - 6x2 + 11x - 6=> abc = -6 and a + b + c = -6 From abc=-6, find the possibilities of their values: (1,2,-3), (1,-2,3), (-1,2,3), (-1,-2,-3), (1,1,-6), (1,-1,6), (-1,1,6) & (-1,-1,-6) Then find the sum of each set of brackets (making sure you do this for all of them):e.g. 1 + 2 + (-3) = 0 and (-1) + (-2) + (-3) = -6 Now, using a + b + c = -6, eliminate the values which do not work.
In this case, the only set that work are (-1,-2,-3) .
So, giving us (x-1)(x-2)(x-3) = 0
To find x solve each bracket:=> x-1=0, x-2=0 & x-3=0 => x=1, x=2 & x=3
Hence, these are the 3 values of x.
[=> means "implies"]

Answered by Ellie-May H. Maths tutor

5461 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Event A: a customer asks for help. Event B a customer makes a purchase. We know: p(B) = 0.2 and p(A) knowing that he has asked for help is 75%. What is the probability of a customer to ask for help and make a purchase?


1. (a) Find the sum of all the integers between 1 and 1000 which are divisible by 7. (b) Hence, or otherwise, evaluate the sum of (7r+2) from r=1 to r=142


How to get A and A* in Maths?


A curve has equation y=x^2 + 2x +5. Find the coordinates of the point at which the gradient is equal to 1.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences